Spotlights on extracellular vesicles in hepatocellular carcinoma diagnosis and treatment: an update review - Wang, Caizheng; Zhang, Xiaoying; Yu, Jiahui; Bu, Jiawen; Gu, Xi; Wang, Yue; Zhu, Xudong; Lin, Jie (Frontiers in Bioengineering and Biotechnology, 2023)
Hepatocellular carcinoma (HCC), one of the most prevalent cancers, with a high mortality rate worldwide, seriously impairs patient health. The lack of accurate targets impedes the early screening and diagnosis of HCC and is associated with a poor response to routine therapies.Extracellular vesicles (EVs), comprising exosomes, microvesicles, and apoptotic bodies, are lipid bilayer membrane-derived nanometer-sized vesicles. EVs can be secreted from various cancer cells and release diverse biomolecules, such as DNA, RNA, proteins, metabolites, and lipids, making them a potential source of biomarkers and regulators of the tumor microenvironment. Emerging evidence suggests that EVs are involved in intercellular communication by carrying biological information.These EVs elicit physiological functions and are involved in the oncogenesis of HCC, such as proliferation, invasion, metastasis, and chemoresistance of HCC. EVs have also been considered promising biomarkers and nanotherapeutic targets for HCC. Therefore, this review sheds light on the current understanding of the interactions between EVs and HCC to propose potential biomarkers and nanotherapeutic strategies.